PENGENALAN PROGRAM “DIET KRESEK” DI PASAR TRADISIONAL UNTUK MEMINIMASI JUMLAH SAMPAH PLASTIK - Umyati, Ani; Herlina, Lely Herlina; Mariawati, Ade Sri (Jurnal Pengabdian Dinamika, 2017)
The problem of plastic waste becomes a complicated problem, especially in big cities. Indonesia. Indonesia is in second in the list of 20 countries that throw the most waste plastic at sea. The top sequence is occupied by China which dumps up to 3.5 million tons of plastic waste to the sea every year. Plastic waste production in Indonesia is ranked second to domestic waste producers, which is 5.4 million tons per year. In 2016, the government through the Ministry of Environment and Forestry has implemented a plastic bag program. The program is expected to limit the use of plastic bags used in modern markets. Buyers are required to pay a sum of money for each used plastic bag. But unfortunately, the rate charged for each plastic bag is still felt too cheap, so the buyers still feel no objection to the cost to be incurred. In addition, the program is only implemented in supermarkets and malls only. Therefore it is necessary to socialize the importance of limiting the use of plastic bags. One way is to provide an understanding to the community to re-use shopping bags that can be used repeatedly. Community service aims to provide an overview and understanding of the dangers of plastic waste. So the community is moved to participate in the program limiting the use of plastic bags, that is by re-use shopping bags that can be used repeatedly.